2015
DOI: 10.1016/j.ccr.2014.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond photoswitching dynamics and microsecond thermal conversion driven by laser heating in FeIII spin-crossover solids

Abstract: Contents 1 Introduction 2 The different thermal spin crossover of the investigated Fe(III) compounds 3Ultrafast photoswitching 3.1 Results 3.2 Discussion 4Spin-state switching driven by lattice expansion and heating 4.1 Results 4.2 Discussion 4.3 Comparison between strongly and weakly cooperative crystals 5 Conclusion 6 Experimental section Acknowledgements References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 79 publications
3
52
1
Order By: Relevance
“…Some reports have demonstrated that the photoexcitation of the LS state inside the thermal hysteresis can generate the HS phase [7,8,9] 4 )]} (pz=pyrazine) compound studied here was evidenced by Bousseksou et al by Raman, optical spectroscopy and magnetic measurements [9][10][11][12]. In crystals, the photoinduced out-of-equilibrium dynamics initiated by a laser pulse involves several steps [13][14][15][16][17][18]. First the LS to HS photoswitching occurs [6,[19][20]: the photoexcited molecules are trapped within less than 200 femtoseconds in the HS potential by the ultrafast activation and damping of the molecular breathing phonon, through a coherent structural reorganization [21][22][23].…”
Section: Fementioning
confidence: 99%
See 3 more Smart Citations
“…Some reports have demonstrated that the photoexcitation of the LS state inside the thermal hysteresis can generate the HS phase [7,8,9] 4 )]} (pz=pyrazine) compound studied here was evidenced by Bousseksou et al by Raman, optical spectroscopy and magnetic measurements [9][10][11][12]. In crystals, the photoinduced out-of-equilibrium dynamics initiated by a laser pulse involves several steps [13][14][15][16][17][18]. First the LS to HS photoswitching occurs [6,[19][20]: the photoexcited molecules are trapped within less than 200 femtoseconds in the HS potential by the ultrafast activation and damping of the molecular breathing phonon, through a coherent structural reorganization [21][22][23].…”
Section: Fementioning
confidence: 99%
“…A 10 mJ laser excites the crystal in the pure LS phase at 293 K (point A on the ascending branch of the hysteresis). It warms up the crystal transiently up to ≈ 313 K, where the full HS state is reached (point B) within less than 1 ms [13][14][15][16][17][18]. This is too fast for our standard camera and we could only observe the crystal, with a colour characteristic of the HS state, 20 ms after laser excitation (point C).…”
Section: 3effect Of Laser Energy and Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8] This has been attributed to a smaller elongation of the Fe-ligand distance, relative to that of Fe II , which lead to a short lifetime of the photoinduced metastable state. 4,5,9 To prevent this fast relaxation from a metastable state to the ground state, a severe distortion of the metal coordination environment, in conjunction with the introduction of extensive intermolecular π-π interactions, has been proposed. 5 (6), and 3.731(7) Å, that are 15, 13, and 11 % shorter than the sum of the van der Waals and ionic radii, respectively.…”
mentioning
confidence: 99%